A template to build an e-commerce web-based application - Hong, Jane Hui Ping (2019)
Since the turning of the century, the world has transitioned into an increasingly connected and web savvy society. Together with the fast-paced lifestyle that society faces today, there is little time to spare for physical shopping. As a result, internet shopping has steadily gained traction and has become an integral part of our lives. With the invention of smartphones and tablets, what would have once been limited to a laptop can now be easily done on a phone. A laptop, smart phone or tablet coupled with an internet connection is all one will need to be able to enjoy the comfort that online shopping provides. Hence the main objective of the project is to create a template from which merchants are able to build an E-commerce web application. The design process takes into consideration building a responsive website that has a user-friendly interface which will provide a good user experience for the users.